Challenges in identifying cancer genes by analysis of exome sequencing data - Matan Hofree (Nature Portfolio, 2016)
Next generation sequencing has been pivotal in identifying somatic mutations in cancer samples. In this study, the authors analyse whole exome sequencing data using a variety of bioinformatic methods to identify mutations in known cancer genes and find that many cancer genes are not detected by these methods.